Neuroimaging of aggressive and violent behaviour in children and adolescents - Sterzer, Philipp; Stadler, Christina (Frontiers in Behavioral Neuroscience, 2009)
In recent years, a number of functional and structural neuroimaging studies have investigated the neural bases of aggressive and violent behaviour in children and adolescents. Most functional neuroimaging studies have persued the hypothesis that pathological aggression is a consequence of deficits in the neural circuits involved in emotion processing. There is converging evidence for abnormal neural responses to emotional stimuli in youths with a propensity towards aggressive behaviour. In addition, recent neuroimaging work has suggested that aggressive behaviour is also associated with abnormalities in neural processes that subserve both the inhibitory control of behaviour and the flexible adaptation of behaviour in accord with reinforcement information. Structural neuroimaging studies in children and adolescents with conduct problems are still scarce, but point to deficits in brain structures in volved in the processing of social information and in the regulation of social and goal-directed behaviour. The indisputable progress that this research field has made in recent years notwithstanding, the overall picture is still rather patchy and there are inconsistencies between studies that await clarification. Despite this, we attempt to provide an integrated view on the neural abnormalities that may contribute to various forms of juvenile aggression and violence, and discuss research strategies that may help to provide a more profound understanding of these important issues in the future.